Comparison the effects of finerenone and SGLT2i on cardiovascular and renal outcomes in patients with type 2 diabetes mellitus: A network meta-analysis - Li, Xuefeng; Wu, Hongli; Peng, Huifang; Jiang, Hongwei (Frontiers in Endocrinology, 2022)
Background: Finerenone and sodium-glucose cotransporter 2 inhibitors (SGLT2i) have been shown to improve cardiovascular and renal outcomes in patients with type 2 diabetes mellitus (T2DM), while the relative efficacy has not been determined. Methods: The databases of PubMed, Embase and Cochrane were searched for relevant cardiovascular or renal outcome trials of SGLT2i or finerenone. The end points were major adverse cardiovascular events (MACE), nonfatal stroke (NS), myocardial infarction (MI), hospitalization for heart failure (HHF), cardiovascular death (CVD), and renal composite outcome (RCO). Network meta-analysis was performed using Bayesian networks to obtain pooled hazard ratios (HR) and 95% confidence intervals (CI). The probability values for ranking active and placebo interventions were calculated using cumulative ranking curves. Results: 1024 articles were searched, and only 9 studies were screened and included in this meta-analysis with 71793 randomized participants. Sotagliflozin (HR 0.72 95%CI 0.59-0.88, SUCAR=0.93) and canagliflozin (HR 0.80 95%CI 0.67-0.97, SUCAR=0.73) can significantly reduce the risk of MACE compared with placebo. Canagliflozin (HR 0.64 95%CI 0.48-0.86, SUCAR=0.73), sotagliflozin (HR 0.66 95%CI 0.50-0.87, SUCAR=0.69) and empagliflozin (HR 0.65 95%CI 0.43-0.98, SUCAR=0.68) can significantly reduce the risk of HHF compared with placebo. Empagliflozin (HR 0.62 95%CI 0.43-0.89, SUCAR=0.96) can significantly reduce the risk of CVD compared with placebo. Empagliflozin (HR 0.61 95%CI 0.39-0.96, SUCAR=0.74), canagliflozin (HR 0.66 95%CI 0.46-0.92, SUCAR=0.63), and dapagliflozin (HR 0.53 95%CI 0.32-0.85, SUCAR=0.88) can significantly reduce the risk of RCO compared with placebo. Finerenone has reduced the risk of MACE, MI, HHF, CVD and RCO to varying degrees, but they do not show significant difference from placebo and each SGLT2i. Conclusion: Both SGLT2i and finerenone could reduce the risk of MACE, HHF, MI, CVD, RCO. Finerenone has no obvious advantage than SGLT2i on the effects of cardiovascular and renal protective.